Evolutionary psychology and consumer behavior: A constructive critique - Cohen, Joel B.; Bernard, H. Russell (Journal of Consumer Psychology, 2013)
Abstract We examine the theoretical basis for the evolutionary narrative common to the target papers by Saad (this issue) and by Griskevicius and Kenrick (this issue) and identify areas of controversy that have sparked debate about evolutionary psychology [EP] among biologists and behavioral ecologists. The two main areas of disagreement are over (1) the role of genetic adaptations resulting from natural selection in ancient times compared to other forces leading to current behavior; and (2) the likelihood that evolution resulted in a set of highly specialized mental modules or information‐processing circuits thought to be instrumental in determining present‐day behavior. We review the EP research discussed by the authors of the target papers as a means of evaluating the evidence in support of the theory and of suggesting future directions of research.